CCDA 640-864 official cert guide - Bruno, A. Anthony (Cisco Press, 2011)
"CCDA 640-864 Official Cert Guide, Fourth Edition is a comprehensive self-study tool for preparing for the new DESGN exam. Complete coverage of all exam topics as posted on the exam topic blueprint ensures you will arrive at a thorough understanding of what you need to master to succeed on the exam. The book follows a logical organization of the DESGN exam objectives. Material is presented in a concise manner, focusing on increasing readers' retention and recall of exam topics. This book helps you organize your exam preparation through the use of the consistent features ..."--Resource description page.